BIMANUAL MICROINCISION VITREOUS SURGERY FOR SEVERE PROLIFERATIVE DIABETIC RETINOPATHY: OUTCOME IN MORE THAN 300 EYES. (September 2018) - Shroff, Cyrus M.; Gupta, Charu; Shroff, Daraius; Atri, Neelam; Gupta, Priyanka; Dutta, Ranjan
Abstract : Purpose: To evaluate the visual and anatomical outcomes and safety of bimanual microincision vitreous surgery for severe proliferative diabetic retinopathy. Methods: Retrospective review of 315 eyes of 282 patients who underwent 23-gauge or 25-gauge pars plana vitrectomy with bimanual membrane dissection for diabetic tractional detachment from January 2007 to September 2016. Minimum follow-up was 3 months, and the average duration of follow-up was 23 months (range 3–100 months; median 15 months). Outcome measures were best-corrected visual acuity, anatomical success, and postoperative complications. Results: Postoperatively, 84.3% of eyes improved (>2 lines), 10.5% were stable, and 5.4% worsened (>2 lines). Comparing gauges, two-line improvement was seen in 87.4% of 23-gauge eyes compared with 79.7% of 25-gauge eyes ( P = 0.029). Mean peak best-corrected visual acuity improved from 20/930 (1.67 ± 0.63) preoperatively to 20/120 (0.78 ± 0.63) postoperatively ( P < 0.001). Primary reattachment was achieved in 310 eyes (98.4%) and final reattachment in 312 eyes (99%). Recurrent vitreous hemorrhage was the commonest postoperative complication (18.4%). Lower incidence of recurrent vitreous hemorrhage was seen with 25 gauge (13.5%) compared with 23 gauge (22%, P = 0.038). Epiretinal membrane formation (7.9%), intractable glaucoma (2.5%), and endophthalmitis (0.6%) were some of the other postoperative complications. Conclusion: Sustained visual improvement, anatomical restoration, and low complication rates were obtained in complex situations with bimanual microincision vitreous surgery in a large series. Visual outcomes were poorer in older age group, tractional retinal detachments involving macula, and eyes with extensive membranes and with silicone oil as tamponade. Both 23-gauge and 25-gauge groups were comparable in relation to visual improvement, anatomical success, and intraoperative and postoperative complications. Abstract : In a series of 315 eyes, bimanual microincision vitreous surgery was found to be a safe and effective technique for complex diabetic vitreoretinal pathologies. Both 23 and 25 gauges had similar results. Older age, macular tractional retinal detachment and combined tractional rhegmatogenous retinal detachment, extensive membranes, and use of silicone oil tamponade correlated with poorer visual recovery.